O USO DO MERCADO DE CARBONO COMO FONTE DE FINANCIAMENTO PARA O DESENVOLVIMENTO DE ÁREAS AGRÍCOLAS: ESTUDO DE CASO DE PEQUENAS PROPRIEDADES DE PASTAGEM NO CENTRO-NORTE FLUMINENSE. - Chagas, Fabiano Oliveira (2010)
This research has an objective to analyze within the Local Development with eucalyptus reforestation on lands used for grazing, having as a financial source the Carbon Credits Market through the Clean Development Mechanism (CDM) projects, as well as support market demand for the charcoal for siderurgic activities. This research studies the possibility of implanting an environmental project with socialeconomic benefits. The study analyzes the cash-flow of the small-scale cattle operations for meat and milk, and simulates the eucalyptus plantation in this kind of farm, considering a longterm planning for cutting the trees and selling to siderurgic charcoal production. The scenario involves familiar-structured farms with small and medium land sizes whose unique source of income is the cattle operations for meat and milk, in centralnorth of Rio de Janeiro comprising Macaé, Conceição de Macabu, Quissamã and Carapebus. The Net Present Value (NPV) analysis, considering the eucalyptus plantation for energetic purposes results in positives values, proofing that this forestry plan is a profitable activity. The methodology AR-AMS0001, approved by the executive board of the United Nation Convention on Climate Change, was used to calculate the additionality resulting from this CDM project. With this additionality the income obtained from the Certified Emission Reductions (CER) market associated with the selling the wood to the siderurgic charcoal market, is of great economical value in comparison with the cattle operations for meat and milk, cash-flow. This increase on the incomes brings profits to underused lands in addition to encouraging the reduction of rural exodus and increase the collection of taxes.